Artificial Intelligence based models for water management and pest management - Jain, Rajni (Indian Farming, 2019)
Agriculture needs help in handling the complexity, uncertainty and fuzziness inherent in its nature, and it requires new solutions for all aspects of agricultural production—from better and predictable crop planning, to precision farming, optimized resource application, support of efficient and collaborative processes using modern technology, fully or partially autonomous solutions for tedious work, up to the sustained long-term development of useful knowledge resources. In the recent decade, automated responses to such challenges in agriculture have been made possible with the help of GPS and mobile communication technology, which provide precise location data and offer the basis of all kinds of location-specific support. Making sense from the data that become available now, and using the resulting knowledge for process and operation improvement on all levels, brings into play Artificial Intelligence and their modelling and reasoning capabilities.